(untitled) (CIPEEX, 2023)
The cardiopulmonary exercise test (CPET) plays a fundamental role in prognostic assessment. In this context, a new parameter known as the cardiorespiratory optimal point (COP) has recently emerged. The POC is defined as the lowest value of the ventilatory equivalent of oxygen (V’E/V’O2) in a given minute during incremental exercise and represents the point of maximum efficiency between the circulatory and respiratory systems. The present research consists of comparing the dynamics of the POC between control individuals (CTL), individuals with Chronic Obstructive Pulmonary Disease (COPD), and individuals with Heart Failure with Reduced Ejection Fraction (HFrEF). Furthermore, it seeks to investigate the potential correlation between POC and peak oxygen consumption (V’O2peak). The V’O2peak showed significant differences (p < 0.001) between the groups, with values of 1825.31 ± 621.75 for CTL, 1057.03 ± 350.45 for COPD, and 1334.52 ± 499.77 ml for HFrEF. Regarding the POC values, the CTL group (24.32 ± 4.10) showed a statistically significant difference (P < 0.001) compared to the other groups, DPOC (28.89 ± 6.78) and ICFEr (28.84 ± 5.53). However, when comparing the DPOC and ICFEr groups, no significant differences (P = 0.998) were found between them. The correlation coefficient between POC and V’O2peak was -0.578 (P < 0.001), indicating a negative association between the analyzed variables, POC and V’O2peak. POC tends to be higher in individuals with compromised health, specifically in those with HFrEF and COPD. Furthermore, there is a significant correlation between the POC variables and V’O2peak.